Studi on The Efficiency Using Nature Materials in The Structural Elements of Reinforced Concrete Beam - . Yasser; Herman Parung; M. Wihardi Tjaronge; Rudy Djamaluddin (Bandar Lampung University (UBL), 2013)
In general bending loads acting on structural elements of concrete beams are retained by the compression area on its pressured area while its drag area is being ignored. Therefore, it is reasonable if the concrete beam section on drag area is minimized with concrete mass reduction in tensile region by ignoring concrete tensile stress while receiving static loads or the area is filled with styrofoam concrete (styrocon). One effort to make efficient the concrete economic value is by reducing concrete and using styrocon thus natural material component such as sand mining, coarse aggregate, and cement and heavy construction becomes lighter. Styrofoam as waste can be used as filler to reduce the volume of concrete, especially for areas where the concrete section is not working mechanically. In an effort to study the flexural strength of concrete beams external reinforcement and composite Styrofoam filled, then a series of tests performed. Test material is in the form of blocks of 15 cm x 20 cm x 270 cm in dimension. Test material is consisted of concrete quality normal beam of 26.0 MPa with transverse reinforcement as a control of test material and the test material with external transverse reinforcement, as well as truss systems and Styrofoam filled composite. The normal-styrocon composite is beam with Styrofoam variation content. The beam is placed on 2 simple pedestal by 2 point loading method testing. The results indicated that normal concrete beam flexural strength is 36.7 kN, but the external transverse reinforcement beams decreased to 30.6 kN, but the external reinforcement beam truss system reinforcement is relatively equal to 35.8 kN. However, the beams with external reinforcement is susceptible to corrosion, fire resistant, and requires treatment. Therefore styrocon is used on the outer portion with styrofoam content of 30%, 40%, and 50% relatively having flexural strengths of 33.8 kN, 31.0 kN and 29.0 kN, respectively. It can be concluded that the use of normal-styrocon composite concrete beams can make efficient the use of natural materials of the concrete block and to reduce the weight construction as well as has environmental aspects by using the waste.